EVALUATION OF FORECASTING METHODS FOR PHOTOVOLTAIC SYSTEMS IN TERMS OF ACCURACY AND COMPUTATIONAL REQUIREMENTS: EVALUATION OF FORECASTING METHODS FOR PHOTOVOLTAIC SYSTEMS IN TERMS OF ACCURACY AND COMPUTATIONAL REQUIREMENTS - Ivanova, Iliyana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Forecasting photovoltaic (PV) production is an essential component for the successful integration of renewable energy into electricity grids. In this paper, four main groups of methods are evaluated: statistical, physical, machine learning-based, and hybrid. An analysis is made in terms of accuracy, computational complexity and applicability using an evaluation scale. The results show that hybrid models appear particularly promising, as they combine the main strengths of the other approaches.